TEKNIK COPYWRITING DALAM TEKNIK SEARCH ENGINE OPTIMIZATION OLEH PT. PAMUJI MEDIA INFOTAMA PADA BULAN DESEMBER 2021 - Haidar, Muhammad Afif; Sarjomo, Herning Suryo; Siswanta, Siswanta (Solidaritas, 2024)
PT Pamuji is a company that operates in the field of information technology and content. Pamuji also provides website creation services with varied article content according to the needs of its clients. Copywriting is used in various social media, such as advertisements, blogs, taglines, articles, or captions on social media. Copywriting uses website media as a tool for promotion and growing consumer interest in a product. To produce good articles, copywriting development using SEO Search Engine Optimization techniques is needed by a copywriter. In this research, the author wants to know and describe the process of creating article content that was created by a copywriter using SEO techniques by PT Pamuji Media Infotama. This research uses a qualitative descriptive approach to describe and explain the activities or events in the research. Descriptive studies collect data in the form of words, and not numbers. Pamuji Media Infotama as a content creation service provider for this website creates content that will be displayed on its client's website through copywriting with Search Engine Optimization techniques by collecting data and processing the data, the data can be in the form of research results. PT. Pamuji Media Infotama is also able to provide education in the content of its copywriting articles in the form of tips and also product selection for its clients so that it becomes a value in itself that can increase readers' interest in making the best choices. Keywords: Content Website, Copywriting, Search Engine Optimization